Implementation of Shar'u Man Qablanā in Fatwa of Indonesian Ulama Council - Ade Nur Rohim; Mustofa; I Nurol Aen (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the concept of syar’u man qablanā and its position as a source of Islamic law, examined from various perspectives of fiqh scholars. There are still differences in the various views of fiqh scholars regarding the position of syar’u man qablanāas, a source of Islamic law, particularly as a basis for establishing fatwas. Furthermore, this study also examines the application of syar’u man qablanā as a basis for establishing fatwas by the Indonesian Ulama Council. This used qualitative method, employing a literature review with discourse analysis and adopting a normative research approach through the utilization of the statute and conceptual approaches. This study concludes that the scholars agree that syar’u man qablanā, which is not explained in the Qur'an does not apply to the people of the Prophet Muhammad. As for the syar’u man qablanā which is not mentioned in the Qur'an, the scholars have several views in concluding it. Indonesian Ulama Council has made at least nine verses of the Qur'an containing syar’u man qablanā as a basis for establishing several fatwas, such as fatwas concerning ijarah, syarī’ah card, multiservice financing, kafalah, syarīa factoring, and other fatwas related to the contemporary transactions. This study contributes to strengthening the study of the implementation of syar’u man qablanā as a basis for establishing Islamic law, especially in determining fatwas by contemporary scholars